The Principle of Individualization in the Communicative Method of Teaching English - Rajabboevna, Alimova Nozima (International Journal on Integrated Education, 2023)
The article explains the essence of the principle of individualization. An assessment of its role and significance in teaching foreign languages is given. The main types of individualization and practical ways of applying this principle in the communicative approach are analyzed. The article may be of interest to teachers of foreign languages.